2018
DOI: 10.1111/jcpp.12936
|View full text |Cite
|
Sign up to set email alerts
|

Early caregiving predicts attachment representations in adolescence: findings from two longitudinal studies

Abstract: Parental sensitive responding in childhood has enduring effects on attachment representation in adolescence, independent of current parenting relationship quality. These findings provide important new evidence supporting early parenting interventions for promoting youth well-being and adjustment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 63 publications
1
17
0
1
Order By: Relevance
“…In addition, in future investigations, it would be interesting to enlarge and diversify the sample used, including longitudinal measurements taken at different times. This would make it possible to conduct causality studies and to more safely locate the variables that influence adolescent well-being [24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, in future investigations, it would be interesting to enlarge and diversify the sample used, including longitudinal measurements taken at different times. This would make it possible to conduct causality studies and to more safely locate the variables that influence adolescent well-being [24].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the emotional bonds established between a baby and its primary caregivers during early childhood might be influencing the future mental scheme teenagers form about themselves and the world around them [22,23]. Children whose primary caregivers, usually the mother and the father, were sensitive and responded appropriately to their needs, establish a bond of secure parental attachment and, as a consequence, foster a basic attitude of trust towards others [24]. From adolescence to mid-life, this could translate into more fluid and positive interpersonal relationships, thanks to more effective emotional and interpersonal skills [23,25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research suggests that individual differences in adolescent attachment security can be traced to earlier caregiving quality (O'Connor, Woolgar, Humayun, Briskman, & Scott, ). Fortunately, there are a number of programmes designed to improve attachment security in young children and accumulating evidence from trials that they are effective (Steele & Steele, ).…”
Section: Discussionmentioning
confidence: 99%
“…Hormonal changes in adolescence push individuals to seek out a romantic partner, shifting the attachment relationship and replacing the parent at the top of the attachment hierarchy (Furman & Wehner, ). Despite this, research has found that early parental sensitivity in childhood is strongly associated with adolescent attachment security (O'Conner, Woolgar, Humayun, Briskman, & Scott, ). Furthermore, there is a strong link between infant attachment styles and adult romantic attachment types (Bartholomew & Horowitz, ).…”
Section: Introductionmentioning
confidence: 99%